Pengembangan Game Edukasi Membaca dan Menulis untuk Meningkatkan Kemampuan Bahasa Aank Usia 5-6 Tahun dalam Keaksaraan Di TK Islam Bhakti 5 YPBWI - Adisa Jasmine Arya (Universitas Muhammadiyah Gresik, 2022)
ABSTRACT This study aims to determine the results of the development of educational gamesto improve language skills in terms of literacy using Power Point, determine the feasibility of educational games (Guess the Picture) Vocabulary Reading and Writing in Indonesian as a learning medium to improve student learning outcomes at Islamic Kindergarten Bhaki 5 YPBWI Gresik based on Power Point, and find out student responses to the use of Power Point-based reading and writing educational games as learning media with basic material of recognizing animal names through a series of vocabulary and then answering the questions listed in the reading and writing educational game, and aims to determine the feasibility of the media as a learning medium. The research method used is development or known as the Research and Development method. The stages in the research process are the analysis, design, development, implementation, and testing stages. The tests carried out are in the form of validation by media and material experts. Then the media was tested by students. After validation has been carried out and the media meets the appropriate interactive criteria, then testing or research is carried out to determine the feasibility in the field. This research was conducted at TK Islam Bhakti 5 YPBWI Gresik involving 17 students. The method used in data collection is a questionnaire, the data obtained is then analyzed by descriptive analysis technique. In this study, the results of the feasibility of media experts on an average of 81% were included in the appropriate category. Material experts on an average of 100% are included in the very feasible category, and the results of student trials are on average 70% and field test results of 79% are very feasible included in the good category. Based on the results of the study, it can be concluded that overall the learning media for developing reading and writing educational games to improve children's language skills in terms of literacy is appropriate to be used as a medium in the learning process in kindergarten group B children. Keywords Development, Eligibility, Learning Media